2019
DOI: 10.1021/acsbiomaterials.9b01362
|View full text |Cite
|
Sign up to set email alerts
|

RGD-Modified Nanocarrier-Mediated Targeted Delivery of HIF-1α-AA Plasmid DNA to Cerebrovascular Endothelial Cells for Ischemic Stroke Treatment

Abstract: Studies have shown that the use of proangiogenic genes can improve the prognosis of ischemic stroke by promoting angiogenesis at the injury site. For example, within this study, hypoxia-inducible factor 1-α (HIF-1α) has exhibited an angiogenic effect. Our previous study reported a more stable HIF-1α mutant form (HIF-1α-AA), which was transfected into mesenchymal stem cells to provide neuroprotective effects against ischemic stroke. The safety of nonviral gene vectors has attracted researchers’ attention. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
(74 reference statements)
1
13
0
Order By: Relevance
“…These results indicated that the modification of RGD significantly enhanced the ischemic brain target of RR@SABNPs, which was attributable to integrin αvβ3. It has been reported that the RGD peptide sequence has a high affinity to integrin αvβ3, 29 , 32 which is involved in angiogenesis after ischemia and expressed in the vessels of both the ischemic core and penumbra but not in the non-ischemic regions. 33 Additionally, a higher fluorescence distribution in the non-ischemic area of RR@SABNPs group which had a slight expression of integrin αvβ3, further demonstrated the advantage of longer circulation time endowed by RBCM coating.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the modification of RGD significantly enhanced the ischemic brain target of RR@SABNPs, which was attributable to integrin αvβ3. It has been reported that the RGD peptide sequence has a high affinity to integrin αvβ3, 29 , 32 which is involved in angiogenesis after ischemia and expressed in the vessels of both the ischemic core and penumbra but not in the non-ischemic regions. 33 Additionally, a higher fluorescence distribution in the non-ischemic area of RR@SABNPs group which had a slight expression of integrin αvβ3, further demonstrated the advantage of longer circulation time endowed by RBCM coating.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo results indicated significant promotion in new blood vessel formation by RGD-DMAPA-Amyp/HIF-1α-AA. The results indicated that RGD-modified NPs are the safe and promising therapeutic strategy for delivering non-viral gene vectors to the brain for ischemic stroke therapy (Deng et al, 2019).…”
Section: Polymeric Nanoparticles In Strokementioning
confidence: 99%
“…The results demonstrated that this nanocomplex had good biocompatibility and could significantly improve the recovery of nerve function and the formation of new blood vessels in vivo. 107 Because many polysaccharides have a high potential for binding to oligonucleotides, nanocarriers formed by peptide functionalized polysaccharides have been used as an effective targeted gene vector into hypoxic cells. These strategies can enhance the efficiency of gene transfection and the therapeutic effect of cancer or ischemic diseases.…”
Section: Peptide Functionalized Polysaccharidesmentioning
confidence: 99%
“…The results demonstrated that this nanocomplex had good biocompatibility and could significantly improve the recovery of nerve function and the formation of new blood vessels in vivo . 107 …”
Section: Peptide Functionalized Polysaccharidesmentioning
confidence: 99%